A diffusion tensor magnetic resonance imaging study of paediatric patients with severe non‐traumatic brain injury. (2nd December 2016) - Molteni, Erika; Rocca, Maria A; Strazzer, Sandra; Pagani, Elisabetta; Colombo, Katia; Arrigoni, Filippo; Boffa, Giacomo; Copetti, Massimiliano; Pastore, Valentina; Filippi, Massimo
Abstract : Aim: In this observational study using 3T magnetic resonance imaging (MRI) and diffusion tensor, we investigated the differential effects of pathology, stage of disease, state of consciousness, and aetiology on the modifications of supra‐ and infra‐tentorial white matter tracts and their correlations with clinical scales in paediatric patients with severe non‐traumatic brain injury. Method: Diffusion tensor magnetic resonance imaging (DT‐MRI) was obtained from seven children with unresponsive wakefulness syndrome (UWS; five males, two females; age at event 5y; standard deviation [SD] 2y 1mo), six children in a minimally conscious state (MCS; three males, three females; age at event 5y 10mo; SD 5y), and 10 healthy children as controls(two males, eight females; age at study 10y 10mo; SD 2y 10mo). Fractional anisotropy, mean, axial, and radial diffusivities were calculated for the corpus callosum, inferior, middle (MCP), and superior cerebellar peduncles (SCP). Results: DT‐MRI parameters from corpus callosum and SCP differed between patients and controls. MCP abnormalities were detected in patients presenting non‐traumatic composite aetiology ( n =4) versus those suffering from pure anoxia ( n =9). The supra‐tentorial compartment was more damaged (i.e. decreased fractional anisotropy and increased diffusivities) than the infra‐tentorial one. Correlations were found between DT‐MRI abnormalities and Glasgow Outcome Scale scores. Interpretation: In paediatric UWS/MCS, the severity of clinical disability correlates with white matter tract abnormalities. What this paper adds: In paediatric non‐traumatic brain injury, fractional anisotropy decreases and diffusivities increase. The supra‐tentorial compartment is more affected than the infra‐tentorial one. Fractional anisotropy and diffusivities abnormalities correlate with Glasgow Outcome Scale. Global, rather than focal, damage contributes to clinical severity. This article is commented on by Aoki and Inokuchi on pages121–122 of this issue.